THE ROLE OF CORPORATE GOVERNANCE ON FINANCIAL STATEMENT QUALITY AND INVESTOR REACTION - Pratiwi, Devica; Syane Mulyawan; Zefanya Evans Lino (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The purpose of this paper is to examine the effect of the number of boards of directors, boards of commissioners, audit committees, the background of the audit committee on the quality of financial statements and the reaction of investors with ROA as a control variable. The population in this study is the annual report of banking company listed on the Indonesia Stock Exchange on 2018. The analysis method in this study is the multiple linear regression analysis using SPSS. Based on simultaneous test results, the number of boards of directors, boards of commissioners, audit committees, the background of the audit committee have a significant influence on the investor's reaction to ROA as a control variable, but had no effect on the quality of financial statements.